THE EFFECTS OF DUCK MANURE ON THE GROWTH AND THE RESULT OF SOME GINGER VARIETIES ON PEAT SOIL - Dwi Zulfita, alasiana Mulyadi Safwan (Fakultas Pertanian Universitas Tanjungpura, 2019)
This study aims to see the interaction of ginger varieties with certain doses of duck manure on peat soil. This study was conducted at the Tanjungpura University Faculty of Agriculture Experimental Garden in Pontianak for 4 months starting February 24, 2018 to June 24, 2018. The study used the Factorial pattern Complete Random Design (CRD), consisting of 3 varieties and 3 fertilizer dosage treatment duck manure droppings with 3 replications and 4 plant samples. Ginger varieties used are red ginger, empirical ginger and ginger elephant. Observation variables included plant height (cm), leaf chlorophyll (spad unit), number of leaves per clump (strands), total leaf area (cm2), plant dry weight (g), number of tillers per clump (clump) and number of leaves (strands ) The results showed no interaction between varieties on the observation variables of plant height, number of leaves of the 1st, 2nd, 3rd, 4th month dry weight of plants and fresh weight per clump. Keywords : Ginger, Duck Manure, Varieties